Organic granular plugging agent for CO2-driving high-temperature low-permeation water-sensitive oil deposit and preparation method thereof - WANG LUSHAN; LIU LEI; YANG HUAN; LIU WEI; DING KANGLE; LUO YUE; LI FAN; YAN XUEMIN; XIAO QINGYAN; LUO XIAO (2015)
The invention relates to an organic granular plugging agent for a CO2-driving high-temperature low-permeation water-sensitive oil deposit and a preparation method thereof, and belongs to the technical field of chemical agent application in petroleum drilling engineering. The organic granular plugging agent is characterized by comprising organic phenol, formaldehyde, furfural, para-toluenesulfonic acid, organic alcohol and a dispersing agent; an adopted isolation section plug is a gas: N2 or CO2; the plugging agent is subjected to carbonyl addition and condensation reaction mainly through the raw materials under the action of a catalyst to form a polymer which takes fural as a bridge and furan hydroxymethyl as an end group, and an organic gel granule is synthesized at an atmosphere of acidity or supercritical CO2 through a solution-sol-gel method; and polymer molecules are enlarged to a certain degree with polymerization reaction, and when the polymer molecules are enlarged to exceed solubility, the polymer molecules are condensed with each other to form an organic granule. The organic granular plugging agent provided by the invention is low in viscosity, easy to pump into a stratum, controllable in gelling time and high in strength and controllable in reaction time after being gelled under the condition of normal temperature, and has the characteristics of high temperature resistance, scouring resistance, stability in property and high plugging rate.